1975
DOI: 10.1111/j.1365-2141.1975.tb01807.x
|View full text |Cite
|
Sign up to set email alerts
|

Globin Chain Synthesis in the Greek Type (Aγ) of Hereditary Persistence of Fetal Haemoglobin

Abstract: Globin chain synthesis was studied in a family with both the Greek (Agamma) type of hereditary persistence of fetal haemoglobin and beta thalassaemia. The ratio of alpha/(gamma+beta+delta) chain synthesis in the hereditary persistence of fetal haemoglobin (HPFH) heterozygotes was 0.97 while in the HPFH/beta-thalassaemia heterozygote it was 2.14. However, calculation of the amounts of haemoglobin synthesized per cell suggests that in the HPFH/beta-thalassaemia heterozygote, the beta- and Agamma-chain genes in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
7
0

Year Published

1979
1979
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 21 publications
4
7
0
Order By: Relevance
“…This finding is in agree ment with the data in the literature [26], On the other hand it must be underlined that in the /1-thalassemia trait the production of Hb A attains 12 g%, while in the association reaches only 7 g, the remaining hemoglobin being formed by Hb F; in this way the «/non-«-ratio can reach the values observed in the //-thalassemia heterozygote only by remarkably increasing the y-chain synthesis. These data mean that the //-gene on the HPFH chromosome is not able to compen sate the deficiency in //-chain synthesis, as a normal gene docs, when a //-thalassemia gene is present in trans.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…This finding is in agree ment with the data in the literature [26], On the other hand it must be underlined that in the /1-thalassemia trait the production of Hb A attains 12 g%, while in the association reaches only 7 g, the remaining hemoglobin being formed by Hb F; in this way the «/non-«-ratio can reach the values observed in the //-thalassemia heterozygote only by remarkably increasing the y-chain synthesis. These data mean that the //-gene on the HPFH chromosome is not able to compen sate the deficiency in //-chain synthesis, as a normal gene docs, when a //-thalassemia gene is present in trans.…”
Section: Discussionsupporting
confidence: 81%
“…On the other hand, Sojroniadou el al. [26] have suggested that in the association, the HPFH chromosome is unable to increase the y-chain synthesis and that the depression of the y-genes on the //-thalassemia chromosome is responsible for the increased amount of Hb F; the pres ence of Gy -and ''/-chains in II-l and 11-2 can agree with these hypotheses.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The imbalanced globin chain production, when studied, is less important than in /5-thalassemia [14]. In this family, hemato logical and clinical findings, as well as defective synthesis of non-a-chains, are more severe than in the previous described cases [4,14,22,24,27] and clearly differ ent from heterozygous HPFH [10,17,19,25,28].…”
Section: Discussionmentioning
confidence: 64%
“…Several lines of evidence suggest that c-globin gene transfer should prove curative for the b-thalassaemic patients. For example, compound heterozygotes for b-thalassaemia and deletional HPFH exhibit a very mild phenotype (Weatherall, 2001), compound heterozygotes for b-thalassaemia and a nondeletional HPFH allele exhibit a b-thalassaemia intermedia phenotype (Fessas & Stamatoyannopoulos, 1964;Sofroniadou et al, 1975;Tate et al, 1986), and compound db-thalassaemia/ b-thalassaemia heterozygotes exhibit a b-thalassaemia intermedia to mild phenotypes (Stamatoyannopoulos et al, 1969). Homozygous b 0 -thalassaemia individuals who have also coinherited an unlinked gene for heterocellular HPFH have higher levels of HbF and mild clinical course (Prchal & Stamatoyannopoulos, 1981).…”
Section: Discussionmentioning
confidence: 99%